Two-rooted mandibular second premolars: Case report and survey - Prakash R; Nandini S; Ballal Suma; Kumar Sowmya; Kandaswamy D (Wolters Kluwer Medknow Publications, 2008)
Mandibular premolars have earned the reputation for having an aberrant anatomy. Literature is replete with reports of extra canals in mandibular second premolars, but reports about the incidence of extra roots in these teeth are quite rare. This paper attempts at explaining a rare case of successful endodontic management of a two-rooted mandibular second premolar with diagnostic, inter-operative and postoperative radiographic records along with a substantial data on the incidence of extra roots in these teeth. The standard method of radiographic appraisal was maintained as the criteria for determining the presence of extra roots. Totally, 600 patients were examined for a period of four months by three endodontists. Out of them, eight patients had an extra root in one of the mandibular second premolars and three patients showed a bilateral presence of two roots.